Knowledge, attitudes, and practices toward leishmaniasis and one health: a cross-sectional study among medical and veterinary professionals - Khan, Yasir; Lin, I-Chen; Khan, Sundus; Kanwal, Mehtab; Wajid, Abdul; Khan, Aamir; Noor, Fazal; Almajwal, Ali Madi; Chen, Chien-Chin; Qadeer, Abdul (Frontiers in Veterinary Science, 2025)
Leishmaniasis is a significant zoonotic infection with global health implications, particularly in regions where human and animal health are closely interconnected. This cross-sectional study assessed the knowledge, attitudes, and practices (KAP) of 5,074 participants regarding leishmaniasis and the One Health concept. The socio-demographic data revealed that most respondents were young (82.6%), male (82.3%), and from rural areas (50.8%), with a majority based in Khyber Pakhtunkhwa (57.4%). Veterinary professionals (42.1%) and students (27.4%) constituted the primary respondents, with 32.4% working in government hospitals. Knowledge about leishmaniasis was high, with 97.5% of participants recognizing Leishmania and 86% correctly identifying it as a protozoan disease. The majority (71.8%) believed in the zoonotic transmission of Leishmania from animals to humans. Attitudes toward the One Health concept were positive, with 90.2% of respondents aware of it, and 95.5% acknowledged the zoonotic nature of the disease. Practices for controlling sandfly populations were observed by 56.4% of participants, with bed nets (44.9%) being the most common preventive measure. Results showed that younger participants had significantly better knowledge, attitude, and perception regarding leishmaniasis and One Health compared to older individuals. Veterinarians and government hospital staff demonstrated better KAP toward VL. This study underscores the importance of educational interventions and community-based control measures to enhance understanding and prevention of leishmaniasis, with the One Health approach playing a crucial role.